Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 124566 by bemath last updated on 04/Dec/20

 ∫ (dx/((x+(√(x^2 +1)))^2 ))

dx(x+x2+1)2

Answered by liberty last updated on 05/Dec/20

 ∫ (dx/((x+(√(x^2 +1)))^2 )) = ?  (1/(x+(√(x^2 +1)))) = ((x−(√(x^2 +1)))/(x^2 −(x^2 +1))) = (√(x^2 +1)) −x  ∫ (dx/((x+(√(x^2 +1)))^2 )) = ∫((√(x^2 +1)) −x)^2  dx   ∫ 2x^2 +1−2x(√(x^2 +1)) dx = (2/3)x^3 +x−(2/3)(x^2 +1)(√(x^2 +1)) + c   =(2/3)(x^2 +1)[x−(√(x^2 +1)) ] + c    = (2/3)(x^2 +1)[ ((−1)/(x+(√(x^2 +1)))) ] + c    = −((2(x^2 +1))/(3(x+(√(x^2 +1))))) + c   If ∫_0 ^( ∞)  (dx/((x+(√(x^2 +1)))^2 )) = lim_(p→∞)  −(2/3)[((x^2 +1)/(x+(√(x^2 +1)))) ]_0 ^p    = −(2/3)[ lim_(p→∞)  ((x^2 +1)/(x+(√(x^2 +1)))) −1 ] = −(2/3) [0−1]   = (2/3)

dx(x+x2+1)2=?1x+x2+1=xx2+1x2(x2+1)=x2+1xdx(x+x2+1)2=(x2+1x)2dx2x2+12xx2+1dx=23x3+x23(x2+1)x2+1+c=23(x2+1)[xx2+1]+c=23(x2+1)[1x+x2+1]+c=2(x2+1)3(x+x2+1)+cIf0dx(x+x2+1)2=limp23[x2+1x+x2+1]0p=23[limpx2+1x+x2+11]=23[01]=23

Answered by Dwaipayan Shikari last updated on 04/Dec/20

(1/(x+(√(x^2 +1))))=t  ⇒−(1/(((√(x^2 +1)))(x+(√(x^2 +1)))))=(dt/dx)  =−∫(√(x^2 +1)) tdt     =−∫t(√((((t^2 −1)/(2t)))^2 +1)) dt  =−(1/2)∫(√((t^2 +1)^2 )) =−(1/6)t^3 −(t/2)  =−(1/6)((1/(x+(√(x^2 +1)))))^3 −(1/2)((1/(x+(√(x^2 +1)))))  =(1/6)(x−(√(x^2 +1)))^3 +(1/2)(x−(√(x^2 +1)))+C

1x+x2+1=t1(x2+1)(x+x2+1)=dtdx=x2+1tdt=t(t212t)2+1dt=12(t2+1)2=16t3t2=16(1x+x2+1)312(1x+x2+1)=16(xx2+1)3+12(xx2+1)+C

Answered by Ar Brandon last updated on 04/Dec/20

I=∫(dx/((x+(√(x^2 +1)))^2 ))  t=x+(√(x^2 +1)) , x=((t^2 −1)/(2t)), dx=((t^2 +1)/(2t^2 ))dt  I=∫(1/t^2 )∙((t^2 +1)/(2t^2 ))dt=(1/2)∫{(1/t^2 )+(1/t^4 )}dt     =−(1/2){(1/t)+(1/(3t^3 ))}=−(1/2){(1/(x+(√(x^2 +1))))+(1/3)∙(1/((x+(√(x^2 +1)))^3 ))+C}

I=dx(x+x2+1)2t=x+x2+1,x=t212t,dx=t2+12t2dtI=1t2t2+12t2dt=12{1t2+1t4}dt=12{1t+13t3}=12{1x+x2+1+131(x+x2+1)3+C}

Answered by Ar Brandon last updated on 04/Dec/20

I=∫(dx/((x+(√(x^2 +1)))^2 ))  x=tanθ ⇒ dx=sec^2 θdθ  I=∫((sec^2 θdθ)/((tanθ+(√(tan^2 θ+1)))^2 ))=∫((sec^2 θdθ)/((tanθ+secθ)^2 ))     =∫(dθ/((sinθ+1)^2 ))=∫(((1−sinθ)^2 )/((1−sin^2 θ)^2 ))dθ     =∫{((1−2sinθ+sin^2 θ)/(cos^4 θ))}dθ=∫{((cos^2 θ−2sinθ+2sin^2 θ)/(cos^4 θ))}dθ     =∫sec^2 θdθ+2∫(((−sinθ))/(cos^4 θ))dθ+2∫tan^2 θsec^2 θdθ     =tanθ−(2/(3cos^3 θ))+((2tan^3 θ)/3)+C  where θ=tan^(−1) (x)

I=dx(x+x2+1)2x=tanθdx=sec2θdθI=sec2θdθ(tanθ+tan2θ+1)2=sec2θdθ(tanθ+secθ)2=dθ(sinθ+1)2=(1sinθ)2(1sin2θ)2dθ={12sinθ+sin2θcos4θ}dθ={cos2θ2sinθ+2sin2θcos4θ}dθ=sec2θdθ+2(sinθ)cos4θdθ+2tan2θsec2θdθ=tanθ23cos3θ+2tan3θ3+Cwhereθ=tan1(x)

Terms of Service

Privacy Policy

Contact: info@tinkutara.com